The Effect Of SAKD Implementation, Organizational Commitment, Accounting Internal Control and The Use Of Information Technology On The Quality Of Government Financial Statements Batanghari Regency Area - Ozi Saifirman S; Ratih Kusumastuti (Economos : Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of the application of the regional financial accounting system (SAKD), organizational commitment, internal accounting control, the use of information technology, and the organization of regional equipment (OPD) on the quality of financial statements produced by the local government of Batanghari Regency. This study adopts a quantitative approach method that focuses on numerical analysis to prove the hypothesis of the sample studied. In order to obtain relevant data, researchers used primary data collection techniques by applying three methods, namely questionnaires, interviews, and literature studies, a sample of 39 respondents filled out the questionnaire used to obtain primary data in this study which was then analyzed with SPSS version 25 with multiple linear regression analysis methods. The results showed that the variables of the Regional Financial Accounting System worth 4.554 > 2.032 at a sig of 0.000 < 0.05 which can be concluded affect the quality of the results of regional financial statements as a whole. Organizational Commitment Variable of 3.360 > 2.032 at GIS of 0.002 < 0.05 which explains that the quality of financial statements is affected partially or in whole. Internal Control Accounting variables of -1.154 < 2.032, at a GIS of 0.257 > 0.05, which can be concluded do not have a real influence on the quality of financial statement results. The variable of Information Technology Utilization is valued at 2.236 > 2.032, at a GIS of 0.024 < 0.05, which can be concluded to partially affect the quality of the financial statements produced.